CT imaging selection in acute stroke. Issue 96 (November 2017) - Bouchez, Laurie; Sztajzel, Roman; Vargas, Maria Isabel; Machi, Paolo; Kulcsar, Zsolt; Poletti, Pierre-Alexandre; Pereira, Vitor Mendes; Lövblad, Karl-Olof
Highlights: CT is the technique of choice in acute stroke. CT can detect boith hemorrhage and ischemia. There is additional value to using CT perfusion and angiography. Abstract: Acute stroke has become an increasingly treatable cause of acute neurological deficits. Indeed, over the last two decades, the introduction of first thrombolysis, and now thrombectomy has improved patient outcomes and extended the therapeutic window. Computed tomography has been established as the most simple and readily available technique for the diagnosis and management of patients with acute stroke. Indeed, CT allows easy confirmation or exclusion of acute hemorrhage on the one hand, and on the other hand the early signs are quite reliable in the detection of ischemia. In the early phase the clot can be seen as well as exchanges related to early changes in water concentration in ischemia and the surrounding penumbra. Additional techniques such as angio-CT show the location of the clot and perfusion techniques reveal local hemodynamics as well as potential tissue viability. Newer techniques such as double energy CT and late phase CT should provide information on collateral flow as well as on the presence of early hemorrhagic transformation. All these techniques should thus make available new information on tissue viability, that is indispensable in the choice of revascularization technique. Thus CT techniques allow a quick and reliable triage as well as a finer characterization of the ischemic process. The use of all these CT techniques in an optimal way should help improve patient triage and selection of the most adequate treatment with further improvements in clinical outcomes as a result.